2021
DOI: 10.1257/aer.20191039
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Paternalism? An Experimental Study

Abstract: We study experimentally when, why, and how people intervene in others’ choices. Choice Architects (CAs) construct opportunity sets containing bundles of time-indexed payments for Choosers. CAs frequently prevent impatient choices despite opportunities to provide advice, believing Choosers benefit. They violate common behavioral welfare criteria by removing impatient options even when all payoffs are delayed. CAs intervene not by removing options they wish they could resist when choosing for themselves (mistake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 73 publications
5
29
0
Order By: Relevance
“…From an applied perspective -and in line with the libertarian paternalism approach (Thaler and Sunstein, 2021) -, the nudge interventions evaluated in our paper could be implemented by those who intervene (e.g., government bodies) by strategically targeting those with norm enforcement power with the relevant social information. Given the observed responsiveness of norm enforcers to such interventions, our study adds an additional layer to what choice architects can do to achieve behavior change (Ambuehl et al, 2021). This refers to, for example, environments in which norm enforcers are feed information about factually true descriptive or injunctive norms.…”
Section: Discussionmentioning
confidence: 99%
“…From an applied perspective -and in line with the libertarian paternalism approach (Thaler and Sunstein, 2021) -, the nudge interventions evaluated in our paper could be implemented by those who intervene (e.g., government bodies) by strategically targeting those with norm enforcement power with the relevant social information. Given the observed responsiveness of norm enforcers to such interventions, our study adds an additional layer to what choice architects can do to achieve behavior change (Ambuehl et al, 2021). This refers to, for example, environments in which norm enforcers are feed information about factually true descriptive or injunctive norms.…”
Section: Discussionmentioning
confidence: 99%
“…Though sparse, the current literature on paternalism aligns well with this cognitive track of the EIC-P Model. For instance, studies have found that characteristics of options (B1) such as the degree of certainty or availability of information (Daniels & Zlatev, 2019;Lusk et al, 2013;Martin et al, 2016) influence paternalistic decisions, and so do characteristics of agents (B2) such as confirmation (Banuri et al, 2019) or self-projection bias (Ambuehl et al, 2021;Foerster et al, 2017;Gangadharan et al, 2015;Ifcher & Zarghamee, 2020;Jacobsson et al, 2007;Jacobsson et al, 2007;Lupoli et al, 2018Lupoli et al, , 2020. Likewise, characteristics of targets (B3) such as self-control or cognitive ability have been shown to significantly influence a paternalistic agent's decision-making (Bushong & Gagnon-Bartsch, 2021;Krawczyk & Wozny, 2017;Sheffer et al, 2017;Uhl, 2011).…”
Section: Affective Paternalismmentioning
confidence: 99%
“…Only a sparse literature examines paternalistic decision-making (see Ambuehl et al (2021) for a review), though most of it focuses on the context of the paternalistic decision (like availability of information) or on stable attributes (like personality traits) of the decisionmaker. The role of affect, however, has been ignored so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We first ask what spectators perceive to be a fair way to distribute income in the following scenario: A pair of workers are assigned the task of identifying which letter is next a number on a list. Each worker is assigned a separate independently 1 This article contributes to the experimental literature on paternalism (Ambuehl, Bernheim, and Ockenfels, 2021;Buser, Putterman, and van der Weele, 2016;Durante, Putterman, and Van der Weele, 2014) by considering how the motivation for imposing fairness views upon groups relates to the preferences of the affected. It introduces paternalist and non-paternalist motivation, which differs from the classic notion of paternalism as acting to avoid others from falling in harm's way against their own will (Coons and Weber, 2013;Thaler and Sunstein, 2003).…”
mentioning
confidence: 99%